Adubação da cultura da soja com cinzas de biomassa florestal - Andrade, Edna Aparecida de (2021)
The objective of the present research was to evaluate the potential of using forest biomass ashes a soil acidity corrective and as a fertilizer for soybean crops. Two experiments were conducted, one in the laboratory and the other in field conditions, in an experimental area of Santa Tereza do Oeste, PR. The first experiment consisted of an incubation test, conducted in laboratory. The treatments were generated by a 2x5 factorial scheme with two soils (clayey and sandy) and five doses of forest biomass ashes: 0, 5, 10, 15 and 20t ha-1 , with four replications in a completely randomized design. The experimental unit was placed in polyethylene containers with lids filled with 0.5 kg of soil. After applying the treatments, the soil was moistened close to its field capacity and the containers were closed. After 90 days of incubation, the soil was dried and sieved. The pH in CaCl2, the contents of Ca, Mg, K, P, Cu, Fe, Mn, Zn and the base saturation were determined. In the second experiment, which was conducted under field conditions, five doses of forest biomass ashes applied on the soil surface, without incorporation were evaluated one day after sowing the soybean crop: 0, 5, 10, 15 and 20t ha-1 . The design used was randomized blocks in four replications. The experimental unit consisted of five 2.5 m and 50 cm wide lines. The soybean cultivar evaluated was Nidera 5909 semi-early variety. The levels of macro and micronutrients in the leaves at the time of flowering were analyzed. During the harvest, the plant height, the number of pods per plant, grains per plant, the mass of a thousand grains and the grain yield were evaluated. The data were submitted to analysis of variance and the effect of doses were evaluated by regression analysis, using the statistical program Assistat. The ashes from forest biomass provided correction of soil acidity and increased the levels of phosphorus, potassium, calcium, magnesium, manganese and zinc in both sandy and clayey soils. Fertilizing the soybean crop with forest biomass ashes increased plant height, pod production and grain yield.